The development of an educational checklist for individuals with CHARGE syndrome. (25th June 2021) - Slavin, Lillian J.; Hartshorne, Timothy S.
Abstract : CHARGE syndrome is a rare genetic disorder which can impact every sensory system and is often associated with significant medical, communicative, developmental, and behavioral difficulties. Due to the rarity and complexity of CHARGE syndrome, educators often lack the expertise required to effectively understand and accommodate the needs of these students. Therefore, an educational checklist (i.e. "Checklist") was developed to provide a comprehensive tool that educators and related professionals can utilize to aid in the education of individuals with CHARGE syndrome. The Checklist was developed through collaboration with an international panel of experts; CHARGE Syndrome Research Lab at Central Michigan University (CMU); and a select group consisting of parents, professionals, and state deafblind project employees. The Checklist outlines major CHARGE characteristics, resulting educational needs, team members, consulting professionals, and suggested methods of accommodation. The Checklist may be utilized to develop and inform services for individuals with CHARGE syndrome in the schools.